Hierarchical self-assembly of a bulk metamaterial enables isotropic magnetic permeability at optical frequencies. Issue 6 (19th September 2016) - Gomez-Graña, S.; Le Beulze, A.; Treguer-Delapierre, M.; Mornet, S.; Duguet, E.; Grana, E.; Cloutet, E.; Hadziioannou, G.; Leng, J.; Salmon, J.-B.; Kravets, V. G.; Grigorenko, A. N.; et al.
Abstract : Raspberry-like magnetic nanoclusters are synthesized and self-assembled to form a bulk magnetic metamaterial. Abstract : Raspberry-like magnetic nanoclusters are synthesized and subsequently self-assembled to form a bulk metamaterial exhibiting strong isotropic optical magnetism in visible light. The magnetic response of the nanoclusters (metamolecules) and of the final assembled material are measured by independent optical experiments. The validity of the effective permeability parameter is probed by spectroscopic ellipsometry at variable incidence. Numerical simulations confirm the measurements.